The Influence of Students' Creativity on Science Learning Independence - Putri, Ayunda Dwi Gustami; Hayu, Wiworo Retnadi Rias; Ramdhani, Muhammad Rendi; Muniroh, Luthfiyatul (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
One of the factors that influences learning independence is creativity. The purpose of this study was to determine the effect of student creativity on the independence of learning science in grade IV at SDN Pabuaran 02 Bogor. The method used is quantitative with the type of causal correlation. The population in this study were all grade IV students totaling 156 students. The sample used was 39 students from grade IV. The sampling technique is sample random sampling. The data collection technique used is the assessment of creative work with product assessment and the learning independence observation sheet. The data analysis technique is by using a simple linear regression test formula. Based on the results of the regression test, the value of Y = 17.198 + 0.994X and the correlation value (R) is 0.680 and the coefficient of determination (R Square) which is 0.462 means that there is an influence between student creativity on learning independence of 46.2%. While the significance value is 0.000 <0.05 which means a significant influence related to student creativity on learning independence which means Ho is rejected and Ha is accepted so that it can be seen that there is an influence of student creativity on learning independence in science.